Dynamic Schedule Computation for Time-Aware Shaper in Converged IoT-Cloud Environments - Papathanail, George; Sakellariou, Ilias; Mamatas, Lefteris; Papadimitriou, Panagiotis (International Conference on Intelligence in Next Generation Networks, 2024)
Over the last years, we have seen the emergence of (hyper-)distributed applications, which tend to be provisioned over resources that span IoT devices, IoT gateways, and compute nodes from edge computing infrastructures. The deployment and orchestration of such services benefits from types of IoT middleware, known as Virtual Objects (VOs). However, in order to reap the benefits of VOs, low-latency communication is required between the IoT devices and their associated VOs. To this end, we utilize Time-Sensitive Networking (TSN), which has paved the way for the timely delivery of delay-sensitive traffic. Our main contribution lies in the design and evaluation of a TSN scheduler, which is compliant with the Time-Aware Shaper (TAS). In this respect, we present a constraint programming formulation for the TSN scheduling problem at hand. A salient feature of the proposed TSN scheduler is its ability to compute the schedule periods both efficiently and at small time-scales. The latter is of crucial importance for dynamic conditions, where the association of IoT devices and their virtual counterparts is subject to change.